Mein kleines ABC - Scarry, Richard (Delphin, 1989)
From airplanes to Zelda Mouse at the zoo, the alphabet is only the beginning of adventure for Lowly Worm, Huckle, and their animal neighbors.
Keywords: Deutsch; Alphabet; Animals; German language; Worms